Pembinaan Penghitungan HPP dan Harga Jual Pada UKM Pengrajin Sandal UD Revin Jaya Kota Mojokerto - Utami, Budi; Setyariningsih, Eny; Fajar, Adik Muhammad (Fakultas Ekonomi Universitas Islam Majapahit, 2021)
This assistance to UD Revin Jaya's Shoe SMEs aims to assist this business in determining the cost of production (HPP) and determining the selling price that is competitive with other shoe businesses. The implementation of service activities is carried out in 3 (three) stages, namely the first stage of survey and observation, the second stage is identification of problems and the third stage is the implementation of PkM. In this PkM activity, partners are taught how to determine the selling price based on the calculation of Cost of Production. The method of calculating the Production Staple Price is the full costing method and the variable costing method. Which method the partner will choose, namely the UD Revin Jaya sandal SME, is recommended to be adjusted to business conditions.